2016
DOI: 10.1039/c5ra23294e
|View full text |Cite
|
Sign up to set email alerts
|

Copper supported on MWCNT-guanidine acetic acid@Fe3O4: synthesis, characterization and application as a novel multi-task nanocatalyst for preparation of triazoles and bis(indolyl)methanes in water

Abstract: The synthesis of a new supported copper (Cu) nanocatalyst, with highly dispersed particles, based on magnetic guanidine acetic acid (GAA) functionalized multi-wall carbon nanotubes (MWCNT), Cu/MWCNT-GAA@Fe3O4, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 66 publications
0
17
0
1
Order By: Relevance
“…It can be seen that the Fe 3 O 4 obtained has a highly crystalline cubic spinel structure which agrees with the standard indicative of the cubic spinel structure of Cu-BIA-Si-Fe 3 O 4 . [40] Hence, according to the results obtained from XRD analysis, one can confirm the presence of Cu on organic group moiety in the Cu-BIA-Si-Fe 3 O 4 nanoparticles. The average Fe 3 O 4 and Cu-BIA-Si-Fe 3 O 4 core diameters were calculated to be about 10 and 11.5 nm from the XRD results using Scherrer's equation, D = kλ/βcos θ, where k is a constant (generally considered as 0.94), λ is the wavelength of Cu Ka (1.54 Å), β is the corrected diffraction line full width at half-maximum and θ is Bragg's angle.…”
Section: Xrd Analysismentioning
confidence: 75%
“…It can be seen that the Fe 3 O 4 obtained has a highly crystalline cubic spinel structure which agrees with the standard indicative of the cubic spinel structure of Cu-BIA-Si-Fe 3 O 4 . [40] Hence, according to the results obtained from XRD analysis, one can confirm the presence of Cu on organic group moiety in the Cu-BIA-Si-Fe 3 O 4 nanoparticles. The average Fe 3 O 4 and Cu-BIA-Si-Fe 3 O 4 core diameters were calculated to be about 10 and 11.5 nm from the XRD results using Scherrer's equation, D = kλ/βcos θ, where k is a constant (generally considered as 0.94), λ is the wavelength of Cu Ka (1.54 Å), β is the corrected diffraction line full width at half-maximum and θ is Bragg's angle.…”
Section: Xrd Analysismentioning
confidence: 75%
“…The Cu(I) species reacts with an alkyne to give a copper acetylide. The 1,3‐dipolar cyclization of the resulting Cu acetylide and an organic azide followed by the protonation provide the formation of a triazole and the regeneration of Cu(I) catalyst …”
Section: Resultsmentioning
confidence: 99%
“…Shaabani et al reported the catalytic use of CuNP-tethered magnetite guanidine acetic acid-decorated MWCNTs (Cu/ MWCNTGAA@Fe 3 O 4 ) for the synthesis of bis(indolyl)methanes (276b) via condensation of two equivalents of indoles (88p) and benzaldehydes (21a, Scheme 264) and 1,2,3-triazoles (71b) via 1,3-dipolar cycloaddition using alkynes (48a), azide (66) and lachrymator benzyl bromides (67d, Scheme 265). 477 To synthesized nal NPs, they loaded Fe 3 O 4 NPs on MWCNTs followed by co-ordination with copper using CuCl 2 $2H 2 O. The stability and reusability of the NPs were observed for up to four runs for the click reaction.…”
Section: Bimetallic Np-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%